“The Scrapyard at the End of the Universe”: Waste Spaces as Incubators for Uncanny AI in the Doctor Who Episode “The Doctor’s Wife” - Hess, Anne (Journal of Posthumanism, 2024)
Human society effectively others and marginalizes its waste spaces. This designation as a willingly forgotten, alternate place has inspired sci-fi (screen) writers to (re-)present dumps as sites of subversion in the otherwise ordered fabrics of their secondary worlds. One facet of this othering are the presentations of these spaces as incubators for new, and often dangerous, posthuman forms of life. In the Doctor Who episode “The Doctor’s Wife” (2011, written by Neil Gaiman) one encounters a waste space that gave rise to artificial intelligence. This AI came into being without any direct human intervention, thus subverting any creator’s myths humanity might cling to, but it also created itself out of the (technological and organic) material of the dumps, giving what human society deemed waste a new purpose – a process that even includes the reanimation of corpses.